Institution for Local and Regional Development in Bosnia and Herzegovina - Jasmina Osmankovic; Ademir Nukovic; Denis Zaimovic (European Regional Science Association (ERSA), 2006)
Institution for local and regional development in Bosnia and Herzegovina The aim of this paper is to present the basic concepts and key issues relating to the formation, development and operation of institutions for local and regional development in Bosnia and Herzegovina. To create strong economic regional development need for strong dynamic institutions to plan, coordinate, promote and take action within the regional development. In this paper we study local and regional institution, background and context, legal and political framework, territorial aspects, relation with EU cohesion, relation with EU network, activities, organisation structure, regional and local partners, capacity building, funding and sustainability. The paper is a reserach position and impact the local and regional institutions in the regional economic development of Bosnia and Herzegovina.
Keywords: 330